2011
DOI: 10.1590/s0104-07072011000300016
|View full text |Cite
|
Sign up to set email alerts
|

Câncer de colo do útero: mortalidade em santa catarina - Brasil, 2000 a 2009

Abstract: O câncer de colo do útero no Brasil é a terceira neoplasia mais comum em mulheres e apresenta alta mortalidade. O objetivo foi o de avaliar a mortalidade por câncer de colo do útero, ocorrida no Estado de Santa Catarina, no período de 2000 a 2009. Estudo descritivo de base populacional, com a inclusão de todos os óbitos de mulheres, por câncer de colo do útero. Nos dados coletados do Sistema de Informação de Mortalidade, do Ministério da Saúde brasileiro, foram identificadas 1253 mortes de mulheres associadas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
1
3
0
10
Order By: Relevance
“…In relation to breast cancer, according research conducted in all regions of Brazil showed that mortality begins to grow from the 25 years, focusing on the age group above 45 years (Zapponi and Melo, 2010). In the state of Goias, cervical cancer had higher mortality rates in the age group above 70 years (Santana et al, 2013); another study showed similar data regarding age presented in this study (Arzuaga-Salazar et al, 2011).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In relation to breast cancer, according research conducted in all regions of Brazil showed that mortality begins to grow from the 25 years, focusing on the age group above 45 years (Zapponi and Melo, 2010). In the state of Goias, cervical cancer had higher mortality rates in the age group above 70 years (Santana et al, 2013); another study showed similar data regarding age presented in this study (Arzuaga-Salazar et al, 2011).…”
Section: Discussionsupporting
confidence: 85%
“…The analyzes conducted in this article about the behavior of breast and uterine cancer in the state of Paraná showed higher mortality rates from these causes, when compared with other states (Arzuaga-Salazar et al, 2011;Leao, 2012). These results demonstrate the immediate need for more effective measures to reduce deaths.…”
Section: Discussionmentioning
confidence: 72%
“…According to the Pan-American Health Organization (PAHO) and World Health Organization (WHO), in order to achieve quality standards for the screening of women in regard to cervical cancer, 80% to 85% of the female population should be consistently screened. 20 In the Brazilian context, however, late diagnosis is still the most common situation. It may be attributed to an interaction among factors such as the female population's difficult access to services, limited and inconsistent services or healthcare programs, and lack of experience of the human resources involved in the detection of cancer and health care delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Na braquiterapia intracavitária, opção para o tratamento do câncer cervical, aplicadores são introduzidos nas cavidades do corpo que requer tratamento, irradiando a região de interesse por um intervalo previamente calculado. 4 A paciente a ser submetida à braquiterapia é colocada em posição ginecológica, vestida com um avental de algodão e coberta por um lençol, sendo exposta apenas sua região genital. Ela é orientada a retirar próteses e adornos desnecessários, caso existam, antes de adentrar a sala de tratamento.…”
Section: -2unclassified